Seed priming with Poly-Gamma-Glutamic Acid (γ-PGA) improves rice germination performance under drought conditions - Dueñas, Conrado; Calvio, Cinzia; Slamet-Loedin, Inez Hortense; Susanto, Untung; Macovei, Anca (MDPI, 2024)
Drought poses a significant threat to global food security, particularly impacting rice cultivation during the germination stage. In this study, a soil-based system that utilizes soil moisture content was used to simulate optimal and stress conditions to assess the effect of the specific seed priming protocols on germination. Eleven rice varieties, representative of indica and japonica subspecies, grown in different ecosystems and having diverse nutrient contents, were treated with water or solutions of either poly-gamma-glutamic acid (γ-PGA) or denatured γ-PGA. Collected data regarding germinability and stress indices revealed different drought sensitivity between japonica and indica subspecies and genotype-specific responses to priming. Particularly, γ-PGA improved germination of highly susceptible indica varieties whereas water soaking was more effective for the moderately sensitive japonica varieties. Integrative analyses evidenced differences between biofortified and non-biofortified rice under γ-PGA treatment, suggesting a possible correlation between γ-PGA efficacy and Zn/Fe seed content. These findings underline that priming strategies should be tailored based on genotype and therefore this factor should be always taken under consideration for future works. The current study provides relevant information for optimizing seed priming techniques to sustain the development of drought-resilient crops as a sustainable strategy to address agricultural resilience and safeguard food security amidst environmental challenges.